2014
DOI: 10.1002/bjs.9344
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes after laparoscopic conversion of failed adjustable gastric banding to sleeve gastrectomy or Roux-en-Y gastric bypass

Abstract: LRYGB and LSG are both safe and feasible options for failed or complicated LAGB. In the non-responders group, %EWL was superior for conversion to LRYGB. The surgical morbidity rate was highest in patients having revision for band complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(24 citation statements)
references
References 23 publications
(55 reference statements)
2
20
0
Order By: Relevance
“…Lastly, ASA score ≥3 remained an independent risk factor for overall postoperative morbidity. Higher incidence of postoperative morbidity after revisional laparoscopic or open RYGB is considered to be secondary to intraoperative difficulties to recognize actual anatomy during dissection, complex adhesiolysis during pouch construction, and gastrojejunostomy anastomosis performed on friable and inflamed tissues due to prior dissection [22,[24][25][26][27][28][29][30][31]. Consequently, postoperative morbidity rate has been reported from 11 to 38 % when RYGBP is performed after vertical banded gastroplasty (VBG) and from 6 to 46 % after adjustable gastric banding (AGB) [32][33][34][35][36][37][38][39][40][41].…”
Section: Discussionmentioning
confidence: 96%
“…Lastly, ASA score ≥3 remained an independent risk factor for overall postoperative morbidity. Higher incidence of postoperative morbidity after revisional laparoscopic or open RYGB is considered to be secondary to intraoperative difficulties to recognize actual anatomy during dissection, complex adhesiolysis during pouch construction, and gastrojejunostomy anastomosis performed on friable and inflamed tissues due to prior dissection [22,[24][25][26][27][28][29][30][31]. Consequently, postoperative morbidity rate has been reported from 11 to 38 % when RYGBP is performed after vertical banded gastroplasty (VBG) and from 6 to 46 % after adjustable gastric banding (AGB) [32][33][34][35][36][37][38][39][40][41].…”
Section: Discussionmentioning
confidence: 96%
“…Although SG and RYGB are comparable in terms of perioperative complications and long-term outcomes [18][19][20], SG has more advantages than RYGB. SG is a purely restrictive operation, causes less malabsorption than RYGB, maintains pylorus function, preserves the natural anatomy of the intestinal tract, and results in a lower risk of ulceration.…”
Section: Discussionmentioning
confidence: 99%
“…One study reported that CRYGB was superior to CSG in terms of percentage of excess weight loss (% EWL) (55 vs. 28%, P=0.001) [19]. Another report demonstrated that both CSG and CRYGB were safe procedures with similar %EWL (47.4…”
Section: Discussionmentioning
confidence: 99%
“…There is still controversy regarding whether a complicated LAGB should be managed with conversion to laparoscopic sleeve gastrectomy (LSG) or Roux-en-Y gastric bypass (LRYGB) even in cases of esophageal perforation. Most bariatric surgeons do not consider converting a failed restrictive procedure such as LAGB to another restrictive procedure such as LSG to be a good strategy (22). On the other hand, Foletto et al state at revisional LSG can be considered a good second-line surgical procedure for complicated LAGB (23).…”
Section: Discussionmentioning
confidence: 99%